KURIKULUM BERBASIS CINTA AND ITS ROLE IN STRENGTHENING ISLAMIC CHARACTER EDUCATION IN MADRASAH IBTIDAIYAH - Nicolas David Azizi; Khamdan Choirul Khabib; Ahmad Wahyulil Albab; Ittikhadul Madani; Eni Setyowati (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
Basic education is a fundamental phase in the formation of students’ character and personality, including the instillation of Islamic character values ​​from an early age. However, in practice, education often emphasizes academic achievement rather than the affective and spiritual dimensions. This condition demands a holistic curriculum based on the values ​​of love and compassion. This study aims to analyze in depth the concept, implementation strategies, and implications of a kurikulum berbasis cinta in madrasas. The research method used is qualitative with a case study approach at MIN 3 Tulungagung. Respondents included Islamic Cultural History (SKI) teachers, second and third grade teachers, and two students. Data were collected through observation, interviews, and documentation. Data validity was obtained through triangulation of sources and methods to ensure the validity of the findings. Data analysis was carried out through the process of data condensation, data presentation, and drawing conclusions. The results of the study indicate that: (1) the philosophical foundation of the love-based curriculum is rooted in the principles of rahmatan lil ‘alamin, humanism, and the value of compassion; (2) its implementation is realized through religious habits, integration of love values ​​in learning, co-curricular activities, and the creation of an empathetic and inclusive learning environment; and (3) a love-based curriculum has a positive influence on the formation of student character and on building a harmonious, religious, and humanistic madrasa culture. These findings recommend that a love-based curriculum be an alternative paradigm for contemporary Islamic education that balances the cognitive, affective, and spiritual dimensions.